Antioxidant activity on Oryza sativa and their phytochemical screening and TLC profiing / Zahirah Nor, Hidayah Abu Bakar and Wan Zuraida Wan Mohd Zain - Nor, Zahirah; Abu Bakar, Hidayah; Wan Mohd Zain, Wan Zuraida (Faculty of Plantation and Agrotechnology, 2018)
In the present study, the phytochemical screening, TLC profiling and antioxidant activity were investigate in the two common Oryza sativa variety in Malaysia which MR220 CL2 and MR219 Fanner in Malaysia usually cultivate paddy from variety MR220 CL2 and MR219 because it resistant to the herbicide and have the higher yield. The both variety are planted more than 20season in more than 90% of the planted area in Malaysia. This study aim to determine the presenceof phytochemical screening, best system solvent toward TLC profiling and antioxidant activity. Six sample such as leaves, hull, cuticle, root, stem and panicle were extract with methanol from both variety and use for the further analysis of the presence alkaloid, saponin, flavonoid, tannin and terpenoid for phytochemical screening. TLC study was carried out by using various solvent system of varying polarity of hexane, chloroform, ethyl acetate, and methanol extract. Therefore, antioxidant activity was performed by DPPH (1, 1 diphenyl-2-picryl hydrazyl) radical scavenging method for different extracts of Oryza sativa using different concentration solvent(50,100,150,200,220 and 500 ppm) and Vitamin C and BHA are used as positive antioxidant control. The result showed that leaves and panicle from the both variety' have most of the phytochemical screening and thin layer chromatographic that constituted different polarity compounds with different Revalues. The DPPH free radicals were scavenged by all plant extractsin a concentration that depend on the IC50 value. It appear that all paddy extract have not active in antioxidant activity.